2017
DOI: 10.1590/1809-4430-eng.agric.v37n2p215-225/2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auditory Enrichment (Music) in Pregnant Sows Welfare

Abstract: Studies have shown that the benefits from music can improve the welfare conditions of laboratory, pet and production animals. The study aimed to evaluate the influence of music (Antonio Lucio Vivaldi compositions) on behavior aspects (position, activity, stereotypes, social and agonistic behavior) and physiological responses (respiratory rate and rectal temperature) in gestating sows in individual cages (stage 1), and collective stalls (stage 2). 28 animals were studied, 14 belonged to music group, and 14 to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
9
1
1
Order By: Relevance
“…There has been some evidence of how stereotypic behavior is induced in farm, laboratory, and wild animals kept in a barren environment [55,56,57]. Stereotypies are defined as a simple ritualized, non-functional, repetitive behaviors [58].…”
Section: Welfare Problems In Pigs Resulting From Intensive Productmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some evidence of how stereotypic behavior is induced in farm, laboratory, and wild animals kept in a barren environment [55,56,57]. Stereotypies are defined as a simple ritualized, non-functional, repetitive behaviors [58].…”
Section: Welfare Problems In Pigs Resulting From Intensive Productmentioning
confidence: 99%
“…In addition, the French Agency for Food, Environmental, and Occupational Health and Safety consider chains “acceptable” as an enrichment [73]. In addition to the optimal materials and objects listed in the Commission Recommendation, environmental enrichment may also be a larger space, fragrance, or even music [57,74,75]. Nutrition can be a special enrichment, especially the way it is provided to animals (e.g., hidden in the substrate) may have some key benefits for improving the pigs’ activity [16].…”
Section: Different Types Of Enrichmentmentioning
confidence: 99%
“…Another example is “Four Seasons” by A. Vivaldi, already tested in research on fowl [ 93 ]. In pregnant sows, the piece (played at 71.13 dB) induced deeper relaxation, as evidenced by metrics such as lower respiration rate, less stereotypies and better interactions with humans [ 108 ]. In contrast, piglets did not take well to the piece by the famous violinist—the music proved distressing to the animals and, thus, disrupted their rest [ 106 ].…”
Section: The Use Of Musicmentioning
confidence: 99%
“…Evaluating pregnant sows, Ringgenberg et al (2012) [ 43 ] concluded that stress during this phase reduces maternal care, reducing responses to piglets’ calls and lactation posture. The mixture of sows in group housing represents a stressful event that occurs during the gestation of sows [ 44 ] (Silva, 2016).…”
Section: Discussionmentioning
confidence: 99%